2012
DOI: 10.5194/acpd-12-11317-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On dithiothreitol (DTT) as a measure of oxidative potential for ambient particles: evidence for the importance of soluble transition metals

Abstract: The rate of consumption of dithiothreitol (DTT) is increasingly used to measure the oxidative potential of particulate matter (PM), which has been linked to the adverse health effects of PM. While several quinones are known to be very reactive in the DTT assay, it is unclear what other chemical species might contribute to the loss of DTT in PM extracts. To address this question, we quantify the rate of DTT loss from individual redox-active species that are common in ambient particulate matter. While most past … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
139
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(161 citation statements)
references
References 45 publications
17
139
0
5
Order By: Relevance
“…The metal content in these diesel/biodiesel exhausted particles seems to largely contribute to the ROS production and total oxidative potential measured by the DTT assay. This is also in accordance to the results reported by Shen and Anastasio, 47 Charrier and Anastasio 27 and Aust et al 48 They reported in these studies that transition metals may represent a major determinant of the toxicity of PM. Charrier and Anastasio 27 found a similar result for DTT loss measured in a small set of PM 2.5 samples.…”
Section: Redox Activity Of Enriched Srm1649b Portionssupporting
confidence: 82%
See 3 more Smart Citations
“…The metal content in these diesel/biodiesel exhausted particles seems to largely contribute to the ROS production and total oxidative potential measured by the DTT assay. This is also in accordance to the results reported by Shen and Anastasio, 47 Charrier and Anastasio 27 and Aust et al 48 They reported in these studies that transition metals may represent a major determinant of the toxicity of PM. Charrier and Anastasio 27 found a similar result for DTT loss measured in a small set of PM 2.5 samples.…”
Section: Redox Activity Of Enriched Srm1649b Portionssupporting
confidence: 82%
“…This is also in accordance to the results reported by Shen and Anastasio, 47 Charrier and Anastasio 27 and Aust et al 48 They reported in these studies that transition metals may represent a major determinant of the toxicity of PM. Charrier and Anastasio 27 found a similar result for DTT loss measured in a small set of PM 2.5 samples. They estimated that for typical PM 2.5 samples approximately 80% of DTT loss is from transition metals, while quinones account for approximately 20%.…”
Section: Redox Activity Of Enriched Srm1649b Portionssupporting
confidence: 82%
See 2 more Smart Citations
“…This result disagrees with Fang et al (2016) as they found no activity for this source in the OP AA test. Such difference for the biomass burning source may be explained by the two extraction protocols (in water or in a SLF solution) or by the proximity of the biomass source 5 in Chamonix compared to the longer distance transport in Atlanta, that would change the chemistry of the source profile.…”
Section: Intrinsic Opmentioning
confidence: 99%